Design and Evaluation of a Gamified Biology Learning Application for Senior Secondary Students in Ilorin, Nigeria - Ahmed Adedolapo Abdulahi; Ademola Olakunle Oyeyipo; Kperogi Halimat Jummai; Adefowora Theodora Adesola (Universitas Islam Bunga Bangsa Cirebon, 2025)
This study examined the Design and Evaluation of a Gamified Biology Learning App for Senior Secondary Students in Ilorin, Nigeria. The problem addressed is the persistent low achievement of students in biology, attributed to traditional teaching methods that fail to engage learners effectively. The objectives were to develop a gamified learning application for selected biology topics, determine its effect on students' academic performance, and examine students’ attitudes towards the application. The study adopted a quasi-experimental research design using a pretest-posttest control group approach. A total of 80 senior secondary school students were selected through multistage sampling of SS2 students from two senior secondary school in Ilorin Kwara state, which is make up of the experimental and the control group. Data were collected using a Biology Performance Test (BPT) and an Attitude towards Gamified Learning Questionnaire (AGLQ). Findings revealed that students taught with the gamified application performed significantly better than those taught through traditional methods. Additionally, students demonstrated a positive attitude towards the gamified learning experience. Based on the findings, it is recommended that teachers adopt gamified applications to improve learning outcomes in biology. It is suggested that future studies explore the effects of different gamification elements across various science subjects. In conclusion, the integration of gamified learning applications offers a promising approach to enhancing biology education in Nigerian schools.